Wasei eigo (Japlish) pada Buku Teks Bahasa Jepang - Putri, Meira Anggia (Journal of Japanese Language Education and Linguistics, 2018)
This study discusses about wasei eigo in Japanese textbook. Wasei eigo are Japanese language expressions that are coined in Japan from English words, that do not exist in Standard English or their meaning differ from the words from which they were derived. Wasei eigo grows rapidly in Japanese, hence wasei eigo frequently found in Japanese textbook. But, the difference of wasei eigo from Standard English becomes problem in understanding the meaning of wasei eigo itself. This study aimed to identify wasei eigo among loanwords in Japanese textbook. Then, those words were classified based on theory by Shibasaki, Tamaoka and Takatori. By knowing the classification of the wasei eigo hopefully will help Japanese language learners in understanding the use and the meaning of wasei eigo. The type of research is qualitative research with descriptive method. Data sources for this research are Minna no Nihongo Shoukyuu 1 and 2. This study showed that there are 27 wasei eigo found in Japanese textbook (Minna no Nihongo Shoukyuu 1 and 2). This study found that based on Shibasaki theory, there are 5 datas of wasei eigo which are classified to imizurekata, 8 datas are classified to tanshukukata, 1 data is classified to junwaseikata, 4 datas are classified to eigohyougenfuzaikata, 8 datas are classified to imizurekata and tanshukukata, and last 1 data that is classified to other than the four of categories.Keyword: Wasei eigo, japlish, loanwords